Analysis of property price and fluctuation in regional macroeconomic indicators: evidence from Indonesia - Rifki Khoirudin; Pramono Hari Adi; Suharno (Penerbit Universiti Kebangsaan Malaysia, 2025)
This research aims to address instability in the housing/property sector in Indonesia from both the demand and supply sides through examining the influence of various macroeconomic indicators across various regions in the country over the period 2017 to 2022. Panel data analysis was employed, using data sourced from the Central Statistics Agency and Bank Indonesia. The Seemingly Unrelated Regression analysis model was applied. The demand-side variable was represented by the Residential Property Price Index data, while the supply-side variable utilised the Construction Cost Index. On the demand side, the Regency/City Minimum Wage, Non-Ownership Home Ownership Status, Population Size, and Gross Regional Domestic Product per Capita significantly affect the Residential Property Price Index. On the supply side, only the Regency/City Minimum Wage has a significant effect on the Construction Cost Index. The findings indicate that Indonesia’s property is more strongly influenced by demand-side macroeconomic indicators than by supply- side factors. The study provides a benchmark for Indonesian government policies, especially at regional government level, in managing property prices and enhance economic stability.